2017
DOI: 10.1136/bmjoq-2017-000183
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hypothermia in newborns admitted to a neonatal care unit in a large academic hospital in New Delhi, India

Abstract: Neonatal hypothermia is a common and dangerous condition around the world. 70% of neonates born in Kalawati Saran Children’s Hospital in New Delhi, India, and subsequently admitted to the neonatal intensive care unit (NICU) had a temperature below 36.5°C on admission. In July 2016, we formed a team of staff from the labour room, NICU and auxiliary staff to reduce hypothermia in babies transported to our NICU using quality improvement methods. We identified problems related to staff awareness of hypothermia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In another study done in North India, Datta et al 19 found that of all the NICU admissions, only 30% of neonates had body temperature in normal range at time of admission to NICU. Other investigators, both from developed world and developing countries, also have reported high incidence of admission hypothermia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study done in North India, Datta et al 19 found that of all the NICU admissions, only 30% of neonates had body temperature in normal range at time of admission to NICU. Other investigators, both from developed world and developing countries, also have reported high incidence of admission hypothermia.…”
Section: Discussionmentioning
confidence: 96%
“…Use of polyethylene cling wraps, use of caps at delivery, increasing labor room temperature, use of radiant warmer to receive the infant, and education of the staff are the common interventions attempted to improve admission temperature. [14][15][16][18][19][20] However, considering the need for delayed cord clamping and inability to use heat loss barriers for all infants at birth, the need of higher DR temperature to prevent subsequent hypothermia should be emphasized. The fear among the obstetricians, of excessive sweating and increased infections rates, when DR temperature is in the recommended ranges needs to be tested to improve compliance on DR temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have also been found to be effective in India. 28 , 29 Based on our experience of using the F-BNA tool to identify problems and QI methods to address these problems, we propose that this methodology can help in the identification of health system bottlenecks at the facility level, their prioritisation, and improvement in these key areas. This methodology is of prime importance in low- and middle-income countries (LMICs) where resource constraints are a constant problem.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining normothermia (36.5 to 37.5 °C) in neonates from delivery room till discharge, and ensuring thermoregulation at discharge is recommended by the World Health Organization (WHO) and other organizations [2] , [21] , [22] . Hypothermia increases the risk of respiratory distress, hypoglycemia, sepsis and pulmonary hemorrhage in preterm infants [23] , [24] , [25] , [26] , [27] . Despite providing respiratory support and surfactant, prolonged hypothermia in preterm infants increases the mortality for respiratory distress syndrome [26] .…”
Section: Introductionmentioning
confidence: 99%
“…Although observational studies show admission-hypothermia as risk factor for mortality in preterm infants [28] , [29] , [30] , meta-analyses of interventions to decrease admission-hypothermia did not show improved survival [23] . Preventing admission-hypothermia is a key-driver to improve survival of preterm infants in quality improvement studies [27] , [31] , [32] .…”
Section: Introductionmentioning
confidence: 99%